1999
DOI: 10.1289/ehp.99107s1109
|View full text |Cite
|
Sign up to set email alerts
|

Selected phenolic compounds in cultivated plants: ecologic functions, health implications, and modulation by pesticides.

Abstract: Phenolic compounds are widely distributed in the plant kingdom. Plant tissues may contain up to several grams per kilogram. External stimuli such as microbial infections, ultraviolet radiation, and chemical stressors induce their synthesis. The phenolic compounds resveratrol, flavonoids, and furanocoumarins have many ecologic functions and affect human health. Ecologic functions include defense against microbial pathogens and herbivorous animals. Phenolic compounds may have both beneficial and toxic effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(49 citation statements)
references
References 49 publications
0
48
0
1
Order By: Relevance
“…In the work of Rocha et al (2008), there was no difference in fiber content between organic and conventional foods, however, according to Daniel et al (1999), the application of some herbicides can increase or decrease the secondary metabolites content, including total phenols, which leads to an uncertainty in the fiber content of conventional foods in Rocha's work.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the work of Rocha et al (2008), there was no difference in fiber content between organic and conventional foods, however, according to Daniel et al (1999), the application of some herbicides can increase or decrease the secondary metabolites content, including total phenols, which leads to an uncertainty in the fiber content of conventional foods in Rocha's work.…”
Section: Resultsmentioning
confidence: 97%
“…In the other vegetables, it is observed that there was a trend of higher fiber content on crops grown organically even with no significant difference occurred. As lignin is part of the total fiber and its structure contains phenols, it is possible that the type of cultivation may interfere with the increase of phenolic compounds since these compounds are produced by the plant as a defense against pathogens (Daniel et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the content of polyphenols may be expected in vegetable organisms also as reaction against biotic or abiotic stress. The application of pesticides and fertilisers has been previously reported to affect the biosynthesis of phenolics in plants, substituting their action, so that conventionally grown plants generally show a phenol content lower than the same but organically grown varieties [19,20]. …”
Section: Total Phenol Contentmentioning
confidence: 99%
“…Such studies have shown that synthesis of phenolic phytoestrogens, necessary for recruiting soil bacteria for symbiosis, is altered by the application of pesticides (Daniel et al 1999). Herbicide application reduces the total amount of and alters the production levels of multiple phytochemicals in treated plants (Daniel et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have shown that synthesis of phenolic phytoestrogens, necessary for recruiting soil bacteria for symbiosis, is altered by the application of pesticides (Daniel et al 1999). Herbicide application reduces the total amount of and alters the production levels of multiple phytochemicals in treated plants (Daniel et al 1999). These findings are significant because the amount and exact profile of phytochemicals produced by a plant directly correlates with its ability to signal and recruit symbiotic soil bacteria (Daniel et al 1999;Peters and Long 1988).…”
Section: Discussionmentioning
confidence: 99%